Biosecurity in Village and Other Free-Range Poultry—Trying to Square the Circle? - Otte, Joachim; Rushton, Jonathan; Rukambile, Elpidius; Alders, Robyn G. (Frontiers in Veterinary Science, 2021)
Village poultry commonly suffer significant disease related losses and a plethora of biosecurity measures is widely advocated as a means to reduce morbidity and mortality. This paper uses a household economy perspective to assess some ‘economic’ considerations determining biosecurity investments of village poultry keepers. It draws on the 2012/13 Tanzania National Panel Survey (TZ-NPS), which covered 1,228 poultry-keeping households. Disease was the most frequently reported cause of bird losses and, in the majority of households, accounted for more than half of reported bird losses. However, given that poultry rarely contributed more than 10% to total annual household income, for 95% of households the value of birds lost to disease represented less than 10% of annual income. The value placed on poultry within households may vary by gender and the overall figure may mask differential intra-household impacts. The break-even cost for various levels of reduction of disease losses is estimated using a partial budget analysis. Even if achieved at no cost, a 75% reduction in disease-associated mortality would only result in a one percent increase of annual household income. Thus, to the ‘average’ village poultry-keeping household, investments in poultry may not be of high priority, even when cost-effective. Where risks of disease spread impact on the wider community and generate significant externalities, poultry keepers must be supported by wider societal actions rather than being expected to invest in biosecurity for purely personal gain.